Dynamic Simulation and Control of Biohydrogen and Microalgae Cultivation Using Palm Oil Mill Effluents (POME) for Carbon Capture - Yahaya, Emmanuel (Curtin University, 2023)
This research focuses on dynamically simulating and controlling biohydrogen production and microalgae cultivation processes using palm oil mill effluents (POME) for carbon capture. The study aims to optimize these interconnected systems, addressing challenges in non-linear dynamics, parameter estimation, and process control to enhance efficiency and contribute to sustainable carbon capture strategies.